Cellulose plastic material and use method thereof

Through the combination of cellulose powder, inorganic mineral powder, nanofibers and nanocrystals, combined with crosslinking agents, 3D printing and molding processes, the problems of cellulose material processing performance and biocompatibility are solved, and high strength is achieved. Degradable cellulose plastic material.

CN119192687APending Publication Date: 2024-12-27SHANDONG SENXIN ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411393212.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Due to the lack of melting characteristics and plasticity, cellulose materials limit their secondary processing properties. The existing composite materials are still non-naturally degradable and have poor biocompatibility after reducing the amount of resin used.

Method used

The cellulose powder, inorganic mineral powder, cellulose nanofibers, cellulose nanocrystals and cellulose dissolving solution are used to prepare plastic cellulose plastic materials through 3D printing and molding. Achieve green process and long-lived composite materials.

Benefits of technology

Various processing and forming methods of cellulose materials are realized, the density and strength of the material are improved, and the degradability and biocompatibility of the product are ensured.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a cellulose plastic material and a use method thereof. The cellulose plastic material comprises the following raw materials in parts by mass: 10-50 parts of cellulose powder; 1 to 5 parts of inorganic mineral powder; 10 to 50 parts of cellulose nanocrystal; 10 to 60 parts of a cellulose dissolving solution; and 0.5 to 5 parts of a cross-linking agent. On the basis of a cellulose-based material rich in source, the plasticity processing method of the cellulose and the composite material of the cellulose are provided, and the obtained product is green in process, long in service life and capable of being completely and autonomously degraded and has multiple different processing forming modes such as compression molding forming and 3D printing forming.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a cellulose plastic material and a method for using the same. Background Art

[0002] Material processing is the process of converting raw materials into products with specific shapes, properties and uses. With the advancement of science and technology and the growth of industrial demand, material processing technology has continued to develop and formed a variety of common methods. Commonly used methods include casting, forging, extrusion, welding, powder metallurgy, 3D printing, rolling, etc. These methods are usually suitable for metal products or plastic products, and cannot be used for materials that cannot be melted or have no plasticity.

[0003] Cellulose is the most abundant renewable polymer in the world today. Wood, bamboo, cotton, wheat straw, rice straw, coconut shell and bagasse are all important sources of cellulose. It has the characteristics of being renewable, low cost and having excellent biological properties. In terms of industrial applications, wood pulp and cotton pulp can be used with high added value. In addition to the most basic household paper, specialty paper, textile products, cellulose ether, etc., it is also widely used in many fields such as medicine, food, and cosmetics. At the same time, the large number of intramolecular and intermolecular hydrogen bonds and high crystallinity inside cellulose cause cellulose to lack melting properties and good plasticity, which greatly limits the secondary processing performance of cellulose materials. For this reason, rice straw powder, wheat straw powder, wood powder, bamboo powder, etc. have appeared as additives and compounded with resin materials such as polypropylene, polylactic acid, cellulose acetate, and polyethylene to produce "bamboo plastic" and "wood plastic" products, so as to achieve the purpose of reducing the use of resin and protecting the environment. However, although the use of resin materials has been reduced, this composite material is still not naturally degradable and has poor biocompatibility. Therefore, it is necessary to explore new cellulose application methods. Summary of the invention

[0004] In order to solve the above problems, on the one hand, the present application proposes a cellulose plastic material, comprising the following raw materials in parts by weight:

[0005] Cellulose powder: 10-50 parts;

[0006] Inorganic mineral powder: 1-5 parts;

[0007] Cellulose nanofibers: 10-50 parts;

[0008] Cellulose nanocrystals: 10-50 parts;

[0009] Cellulose dissolving solution: 10-60 parts;

[0010] Cross-linking agent: 0.5 to 5 parts. Based on the abundant cellulose-based materials, this application provides a plastic processing method of cellulose and its composite material, the obtained product has green process, long service life, can be completely self-degradable, and has a variety of different processing and molding methods such as compression molding and 3D printing molding.

[0011] Preferably, the mesh size of the cellulose powder is greater than 150 mesh.

[0012] Preferably, the cellulose powder is bleached wood pulp powder, cotton pulp powder, or a combination of any two of them;

[0013] The cellulose powder is prepared as follows: drying the raw material in a vacuum oven at 90-110° C. for 60-110 min;

[0014] The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain cellulose powder with a particle size greater than 150 meshes.

[0015] Preferably, the cellulose dissolving solution is prepared as follows:

[0016] Then, the pulp is placed in a specific solvent system, wherein the mass of the pulp input accounts for 5 to 10 wt% of the total mass of the specific solvent;

[0017] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6-8wt%, and the mass fraction of urea is 6-8wt%; the solvent system is precooled to -12°C to -7°C, the pulp is added in batches, and then stirred for 45-60 minutes to obtain a cellulose solution;

[0018] The pulp is cotton pulp or wood pulp;

[0019] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0020] Preferably, the cellulose nanocrystals are obtained in the following manner:

[0021] The pulp is placed in a sulfuric acid solution with a mass fraction of 40-70wt%, the mass of the pulp is 5-10% of the mass of the sulfuric acid solution, the reaction temperature is 50-105°C, the reaction is stirred for 2-3 hours, then neutralized and washed, homogenized at 500-900bar for 1-3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15-25%.

[0022] Preferably, the following raw materials are also included in parts by weight:

[0023] Cellulose fiber: 5-15 parts;

[0024] Cellulose particles: 10-50 parts;

[0025] The cellulose powder: 10 to 30 parts;

[0026] The cellulose nanofibers: 10 to 20 parts;

[0027] The cellulose nanocrystals: 10 to 20 parts. The cellulose nanofibers of the present application play a complementary role to the cellulose fibers and cellulose nanocrystals in the system, and their presence makes the system denser and stronger.

[0028] Preferably, the cellulose fiber is a mixture of one or more of cotton fiber, paper mulberry fiber, bamboo fiber, and hemp fiber in any proportion, the cellulose fiber has a length of 2 to 20 mm, a diameter of 20 to 1000 μm, and is dried at 45 to 55° C.;

[0029] The cellulose powder includes a first cellulose powder with a particle size greater than 150 meshes, a second cellulose powder with a particle size not greater than 150 meshes and greater than 100 meshes, and a third cellulose powder with a particle size not greater than 100 meshes and greater than 60 meshes, wherein the first cellulose powder accounts for 30-35wt% and the second cellulose powder accounts for 30-35wt%, and the rest is the third cellulose powder;

[0030] The cellulose powder is one or a combination of two or more of straw powder, paper mulberry powder, bamboo powder and coconut shell powder in any proportion;

[0031] The cellulose powder is prepared as follows: drying the raw material in a vacuum oven at 90-110° C. for 60-110 min;

[0032] Then, the dried sample is crushed by a high-speed crusher, and then sieved by a vibration screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder;

[0033] The cellulose fiber is one of cotton fiber, paper mulberry fiber, bamboo fiber, and hemp fiber, or a combination of two or more in any proportion, and the fiber length is 2 to 20 mm and the diameter is 20 to 1000 μm;

[0034] The cellulose particles are bamboo particles, wood particles or a mixture of the two in any proportion, and are crushed by a universal crusher or a wood crusher to a particle size of 5 to 30 mm and dried at 65 to 75°C.

[0035] Preferably, the cross-linking agent is a mixture of one or more of bentonite, polyvinyl alcohol, borax, starch, polyacrylamide, and waterborne polyurethane in any proportion;

[0036] The inorganic mineral powder is a mixture of one or more of quartz sand, talc, montmorillonite, wollastonite, kaolin, magnesium hydroxide and mica in any proportion, and the mesh number is 800-1500 meshes.

[0037] On the other hand, the present application discloses a method for using a cellulose plastic material, comprising the following steps:

[0038] The cellulose solution, cellulose powder, inorganic mineral powder, cellulose nanofibers and cellulose nanocrystals are mixed and stirred evenly;

[0039] Then, a cross-linking agent is added and mixed evenly to obtain an original slurry;

[0040] After degassing the original slurry, load it into the barrel of the 3D printer and print it according to the set program. The diameter of the extrusion nozzle used for printing is 0.5mm, the extrusion pressure is 0.2MPa, and the extrusion nozzle movement speed is 50mm / s;

[0041] The printed sample is placed in a coagulation bath, and after the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, and the drying temperature is 50-90° C. The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12-15wt%, and the mass fraction of sodium sulfate is 18-25wt%;

[0042] Soaking and washing away the residual sulfuric acid and salt in water can obtain the finalized 3D printing material;

[0043] The shaped 3D printing material is placed in a cross-linking solution, wherein the cross-linking solution is K + , Ca 2+ , Fe 3+ 、Zn 2+ , Cu 2+ 、Al 3+ A mixed solution of one or more soluble salts in the mixture is prepared with a concentration of 0.5 to 2 mol / L; the cross-linking temperature is 25 to 35°C for 8 to 12 hours, and then the mixture is washed and dried in a vacuum oven at a temperature of 60 to 90°C for 120 to 300 minutes.

[0044] On the other hand, the present application also discloses another method for using the cellulose plastic material, comprising the following steps:

[0045] The cellulose solution, cellulose powder, inorganic mineral powder, cellulose nanofibers, cellulose nanocrystals, cellulose fibers and cellulose particles are mixed and stirred evenly;

[0046] Then, a cross-linking agent is added and mixed evenly to obtain an original slurry;

[0047] The original slurry is placed in a mold for compression molding to obtain a sample, the molding pressure is 15-30 MPa, and the molding time is 30-100 s;

[0048] The molded sample is immersed in a coagulation bath, and after the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, and the drying temperature is 50-90° C. The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12-15wt%, and the mass fraction of sodium sulfate is 18-25wt%;

[0049] The shaped dried composite material is placed in a vacuum oven for drying at a temperature of 60 to 90° C. for a drying time of 120 to 300 minutes. The present application uses cellulose particles as a substrate. Although the composition is complex, the combination of cellulose solution, cellulose nanofibers, and cellulose nanocrystals can ensure the bonding force between the components of the final product, thereby ensuring the strength of the molded product.

[0050] This application can bring the following beneficial effects:

[0051] 1. This application is based on abundant cellulose-based materials and provides a plastic processing method for cellulose and its composite materials. The resulting product has a green process, a long service life, can be completely self-degradable, and has a variety of different processing and molding methods such as compression molding and 3D printing molding.

[0052] 2. The cellulose nanofibers of the present application complement the cellulose fibers and cellulose nanocrystals in the system, and their presence makes the system denser and stronger.

[0053] 3. The present application uses cellulose particles as a substrate. Although the composition is complex, the combination of cellulose solution, cellulose nanofibers and cellulose nanocrystals can ensure the bonding strength between the various components of the final product, thereby ensuring the strength of the molded product. DETAILED DESCRIPTION

[0054] In order to clearly illustrate the technical features of this solution, this application is elaborated in detail below through specific implementation methods.

[0055] This application actually discloses two cellulose plastic materials and methods of using the same, specifically including 3D printing materials and molding materials;

[0056] 1. For 3D printing materials, the following steps are included:

[0057] S11. Raw material preparation:

[0058] The cellulose powder is one or a combination of bleached wood pulp powder and cotton pulp powder in any proportion;

[0059] The cellulose powder is prepared as follows: drying the raw material in a vacuum oven at 90-110° C. for 60-110 min;

[0060] The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain cellulose powder with a particle size greater than 150 meshes.

[0061] The cellulose dissolving solution is prepared as follows:

[0062] Then, the pulp is placed in a specific solvent system, wherein the mass of the pulp input accounts for 5 to 10 wt% of the total mass of the specific solvent;

[0063] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6-8wt%, and the mass fraction of urea is 6-8wt%. The solvent system is precooled to -12°C to -7°C, the pulp is added in batches, and then stirred for 45-60 minutes to obtain a cellulose solution;

[0064] The pulp is cotton pulp or wood pulp.

[0065] The cellulose nanocrystals are obtained in the following manner:

[0066] The pulp is placed in a sulfuric acid solution with a mass fraction of 40-70wt%, the mass of the pulp is 5-10% of the mass of the sulfuric acid solution, the reaction temperature is 50-105°C, the reaction is stirred for 2-3 hours, then neutralized and washed, homogenized at 500-900bar for 1-3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15-25%.

[0067] The cross-linking agent is a mixture of one or more of bentonite, polyvinyl alcohol, borax, starch, polyacrylamide, and waterborne polyurethane in any proportion;

[0068] The inorganic mineral powder is a mixture of one or more of quartz sand, talc, montmorillonite, wollastonite, kaolin, magnesium hydroxide and mica in any proportion, and the mesh number is 800-1500 meshes.

[0069] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0070] S12. Raw material mixing:

[0071] Mix 10 to 60 parts of cellulose solution, 10 to 50 parts of cellulose nanocrystals (i.e., cellulose nanocrystal slurry), 10 to 50 parts of cellulose powder, and 1 to 5 parts of inorganic mineral powder evenly;

[0072] Then add 0.5 to 5 parts of a cross-linking agent and mix evenly to obtain an original slurry;

[0073] S13.3D printing

[0074] After degassing the original slurry, load it into the barrel of the 3D printer and print it according to the set program. The diameter of the extrusion nozzle used for printing is 0.5mm, the extrusion pressure is 0.2MPa, and the extrusion nozzle movement speed is 50mm / s;

[0075] S14. Post-printing processing

[0076] The printed sample is placed in a coagulation bath and soaked for 40 minutes. After the reaction is completed, it is soaked in clean water and the residual sulfuric acid and salt are washed off to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, the drying temperature is 50-90° C., and the drying time is 3 hours; the coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12-15wt%, and the mass fraction of sodium sulfate is 18-25wt%;

[0077] Soaking and washing away the residual sulfuric acid and salt in water can obtain the finalized 3D printing material;

[0078] The shaped 3D printing material is placed in a cross-linking solution, wherein the cross-linking solution is K + , Ca 2+ , Fe 3+ 、Zn 2+ , Cu 2+ 、Al 3+ A mixed solution of one or more soluble salts in the mixture is prepared with a concentration of 0.5 to 2 mol / L; the cross-linking temperature is 25 to 35°C for 8 to 12 hours, and then the mixture is washed and dried in a vacuum oven at a temperature of 60 to 90°C for 120 to 300 minutes.

[0079] Make the following specific embodiments:

[0080] Embodiment 1:

[0081] S1101. Raw material preparation:

[0082] The cellulose powder is bleached wood pulp powder;

[0083] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 90° C. for 110 min;

[0084] The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain cellulose powder with a particle size greater than 150 meshes.

[0085] The cellulose dissolving solution is prepared as follows:

[0086] Then, the pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass of the specific solvent;

[0087] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0088] The pulp is cotton pulp.

[0089] The cellulose nanocrystals are obtained in the following manner:

[0090] The pulp was placed in a 40wt% sulfuric acid solution, the mass of the pulp was 5% of the mass of the sulfuric acid solution, the reaction temperature was 105°C, the reaction was stirred for 2 hours, then neutralized and washed, homogenized once at 500bar, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15%.

[0091] The cross-linking agent is polyvinyl alcohol;

[0092] The inorganic mineral powder is montmorillonite with a mesh size of 800 to 1500 meshes.

[0093] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0094] S1102. Raw material mixing:

[0095] Mix 10 parts of cellulose solution, 10 parts of cellulose nanocrystals (i.e., cellulose nanocrystal slurry), 10 parts of cellulose powder, and 1 part of inorganic mineral powder evenly;

[0096] Then, 0.5 parts of a cross-linking agent was added and mixed evenly to obtain an original slurry;

[0097] S1103.3D Printing

[0098] After degassing the original slurry, load it into the 3D printer barrel and print it according to the set program. The diameter of the extrusion nozzle used for printing is 0.5mm, the extrusion pressure is 0.2MPa, and the extrusion nozzle movement speed is 50mm / s; the printed vacuum long cylinder has a wall thickness of 1mm, an outer diameter of 50mm, and a length of 200mm;

[0099] S1104. Post-printing processing

[0100] The printed sample is placed in a coagulation bath and soaked for 40 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, the drying temperature is 50°C, and the drying time is 3 hours; the coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12wt% and the mass fraction of sodium sulfate is 18wt%;

[0101] Soaking in water and washing away the residual sulfuric acid and salt will give you a shaped long tube;

[0102] The shaped long tube is placed in a cross-linking solution, wherein the cross-linking solution is K + , Ca 2+ , Fe 3+ 、Zn 2+ , Cu 2+ 、Al 3+ The mixed solution of soluble salts has a concentration of 0.1 mol / L for each ion; the cross-linking temperature is 25°C and the time is 12 hours, and then it is washed and placed in a vacuum oven for drying at a temperature of 60°C and a drying time of 300 minutes.

[0103] The long tube was placed in boiling water. Under the impact of boiling water, the time for the long tube to be significantly deformed was recorded. The average value of the five groups of samples was 27 minutes.

[0104] The two sides of the long tube were clamped, and then slowly stretched at a rate of 20 mm / min until the long tube broke. The maximum tensile force was recorded, and the average value of the five groups of samples was 120 N.

[0105] Embodiment 2:

[0106] S1201. Raw material preparation:

[0107] The cellulose powder is cotton pulp powder;

[0108] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 110° C. for 60 minutes;

[0109] The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain cellulose powder with a particle size greater than 150 meshes.

[0110] The cellulose dissolving solution is prepared as follows:

[0111] Then, the pulp is placed in a specific solvent system, wherein the mass of the pulp input accounts for 5 to 10 wt% of the total mass of the specific solvent;

[0112] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 8wt%, and the mass fraction of urea is 8wt%. The solvent system is precooled to -7°C, the pulp is added in batches, and then stirred for 60 minutes to obtain a cellulose solution;

[0113] The pulp is wood pulp.

[0114] The cellulose nanocrystals are obtained in the following manner:

[0115] The pulp was placed in a 70wt% sulfuric acid solution, the mass of the pulp was 10% of the mass of the sulfuric acid solution, the reaction temperature was 50°C, the reaction was stirred for 3 hours, then neutralized and washed, homogenized at 900bar for 3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 25%.

[0116] The cross-linking agent is starch;

[0117] The inorganic mineral powder is magnesium hydroxide, and the mesh number is 800-1500 meshes.

[0118] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0119] S1202. Raw material mixing:

[0120] Mix 60 parts of cellulose solution, 50 parts of cellulose nanocrystals (i.e., cellulose nanocrystal slurry), 50 parts of cellulose powder, and 5 parts of inorganic mineral powder evenly;

[0121] Then add 5 parts of cross-linking agent and mix well to obtain the original slurry;

[0122] S1203.3D Printing

[0123] After degassing the original slurry, load it into the 3D printer barrel and print it according to the set program. The diameter of the extrusion nozzle used for printing is 0.5mm, the extrusion pressure is 0.2MPa, and the extrusion nozzle movement speed is 50mm / s; the printed vacuum long cylinder has a wall thickness of 1mm, an outer diameter of 50mm, and a length of 200mm;

[0124] S1204. Post-printing processing

[0125] The printed sample is placed in a coagulation bath and soaked for 40 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, the drying temperature is 90°C, and the drying time is 3 hours; the coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 15wt% and the mass fraction of sodium sulfate is 25wt%;

[0126] The long tube can be obtained by soaking it in water and washing away the residual sulfuric acid and salt;

[0127] The long tube is placed in a cross-linking solution, wherein the cross-linking solution is K + , Fe 3+ 、Zn 2+ , Cu 2+ 、Al 3+ A mixed solution of soluble salts in the mixture, each ion concentration is 0.4 mol / L; the cross-linking temperature is 35°C, the time is 8h, and then it is washed and placed in a vacuum oven for drying, the drying temperature is 90°C, and the drying time is 120min.

[0128] The long tube was placed in continuously boiling water. Under the impact of boiling water, the time when the long tube was obviously deformed was recorded. The average value of the five groups of samples was 31 minutes.

[0129] The two sides of the long tube were clamped, and then slowly stretched at a rate of 20 mm / min until the long tube broke. The maximum tensile force was recorded, and the average value of the five groups of samples was 113 N.

[0130] Comparative Example 1:

[0131] S1301. Raw material preparation:

[0132] The cellulose powder is bleached wood pulp powder;

[0133] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 90° C. for 110 min;

[0134] The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain cellulose powder with a particle size greater than 150 meshes.

[0135] The cellulose dissolving solution is prepared as follows:

[0136] Then, the pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass of the specific solvent;

[0137] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0138] The pulp is cotton pulp.

[0139] The cross-linking agent is polyvinyl alcohol;

[0140] The inorganic mineral powder is montmorillonite with a mesh size of 800 to 1500 meshes.

[0141] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0142] S1302. Raw material mixing:

[0143] 10 parts of cellulose solution, 10 parts of cellulose nanocrystals (commercially available, 15 wt% concentration), 10 parts of cellulose powder, and 1 part of inorganic mineral powder were mixed evenly;

[0144] Then, 0.5 parts of a cross-linking agent was added and mixed evenly to obtain an original slurry;

[0145] S1303.3D Printing

[0146] After degassing the original slurry, load it into the 3D printer barrel and print it according to the set program. The diameter of the extrusion nozzle used for printing is 0.5mm, the extrusion pressure is 0.2MPa, and the extrusion nozzle movement speed is 50mm / s; the printed vacuum long cylinder has a wall thickness of 1mm, an outer diameter of 50mm, and a length of 200mm;

[0147] S1304. Post-printing processing

[0148] The printed sample is placed in a coagulation bath and soaked for 40 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, the drying temperature is 50°C, and the drying time is 3 hours; the coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12wt% and the mass fraction of sodium sulfate is 18wt%;

[0149] The long tube can be obtained by soaking it in water and washing away the residual sulfuric acid and salt;

[0150] The long tube is placed in a cross-linking solution, wherein the cross-linking solution is K + , Ca 2+ , Fe 3+ 、Zn 2+ , Cu 2+ 、Al 3+ The mixed solution of soluble salts has a concentration of 0.1 mol / L for each ion; the cross-linking temperature is 25°C and the time is 12 hours, and then it is washed and placed in a vacuum oven for drying at a temperature of 60°C and a drying time of 300 minutes.

[0151] Place the long tube in continuously boiling water. Under the impact of boiling water, record the time when the long tube has obvious deformation. The average value of five groups of samples is 20 minutes.

[0152] The two sides of the long tube were clamped, and then slowly stretched at a rate of 20 mm / min until the long tube broke. The maximum tensile force was recorded, and the average value of the five groups of samples was 101N.

[0153] Comparative Example 2:

[0154] S1401. Raw material preparation:

[0155] The cellulose powder is bleached wood pulp powder;

[0156] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 90° C. for 110 min;

[0157] The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain cellulose powder with a particle size greater than 150 meshes.

[0158] The cellulose dissolving solution is prepared as follows:

[0159] Then, the pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass of the specific solvent;

[0160] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0161] The pulp is cotton pulp.

[0162] The cellulose nanocrystals are obtained in the following manner:

[0163] The pulp was placed in a 40wt% sulfuric acid solution, the mass of the pulp was 5% of the mass of the sulfuric acid solution, the reaction temperature was 105°C, the reaction was stirred for 2 hours, then neutralized and washed, homogenized once at 500bar, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15%.

[0164] The cross-linking agent is polyvinyl alcohol;

[0165] The inorganic mineral powder is montmorillonite with a mesh size of 800 to 1500 meshes.

[0166] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0167] S1402. Raw material mixing:

[0168] Mix 10 parts of cellulose solution, 10 parts of cellulose nanocrystals (i.e., cellulose nanocrystal slurry), 10 parts of cellulose powder, and 1 part of inorganic mineral powder evenly;

[0169] Then, 0.5 parts of a cross-linking agent was added and mixed evenly to obtain an original slurry;

[0170] S1403.3D Printing

[0171] After degassing the original slurry, load it into the 3D printer barrel and print it according to the set program. The diameter of the extrusion nozzle used for printing is 0.5mm, the extrusion pressure is 0.2MPa, and the extrusion nozzle movement speed is 50mm / s; the printed vacuum long cylinder has a wall thickness of 1mm, an outer diameter of 50mm, and a length of 200mm;

[0172] S1404. Post-printing processing

[0173] The printed sample is placed in a coagulation bath and soaked for 40 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, the drying temperature is 50°C, and the drying time is 3 hours; the coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12wt% and the mass fraction of sodium sulfate is 18wt%;

[0174] Soaking in water and washing away the residual sulfuric acid and salt will give you a shaped long tube;

[0175] The long tube was placed in continuously boiling water. Under the impact of boiling water, the time for the long tube to be significantly deformed was recorded. The average value of the five groups of samples was 23 minutes.

[0176] The two sides of the long tube were clamped, and then slowly stretched at a rate of 20 mm / min until the long tube broke. The maximum tensile force was recorded, and the average value of the five groups of samples was 108 N.

[0177] Comparative Example 3:

[0178] S1501. Raw material preparation:

[0179] The cellulose dissolving solution is prepared as follows:

[0180] Then, the pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass of the specific solvent;

[0181] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0182] The pulp is cotton pulp.

[0183] The cellulose nanocrystals are obtained in the following manner:

[0184] The pulp was placed in a 40wt% sulfuric acid solution, the mass of the pulp was 5% of the mass of the sulfuric acid solution, the reaction temperature was 105°C, the reaction was stirred for 2 hours, then neutralized and washed, homogenized once at 500bar, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15%.

[0185] The cross-linking agent is polyvinyl alcohol;

[0186] The inorganic mineral powder is montmorillonite with a mesh size of 800 to 1500 meshes.

[0187] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0188] S1502. Raw material mixing:

[0189] Mix 10 parts of cellulose solution, 10 parts of cellulose nanocrystals (i.e., cellulose nanocrystal slurry), and 1 part of inorganic mineral powder evenly;

[0190] Then, 0.5 parts of a cross-linking agent was added and mixed evenly to obtain an original slurry;

[0191] S1503.3D Printing

[0192] After degassing the original slurry, load it into the 3D printer barrel and print it according to the set program. The diameter of the extrusion nozzle used for printing is 0.5mm, the extrusion pressure is 0.2MPa, and the extrusion nozzle movement speed is 50mm / s; the printed vacuum long cylinder has a wall thickness of 1mm, an outer diameter of 50mm, and a length of 200mm;

[0193] S1504. Post-printing processing

[0194] The printed sample is placed in a coagulation bath and soaked for 40 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, the drying temperature is 50°C, and the drying time is 3 hours; the coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12wt% and the mass fraction of sodium sulfate is 18wt%;

[0195] Soaking in water and washing away the residual sulfuric acid and salt will give you a shaped long tube;

[0196] The shaped long tube is placed in a cross-linking solution, wherein the cross-linking solution is K + , Ca 2+ , Fe 3+ 、Zn 2+ , Cu 2+ 、Al3+ The mixed solution of soluble salts has a concentration of 0.1 mol / L for each ion; the cross-linking temperature is 25°C and the time is 12 hours, and then it is washed and placed in a vacuum oven for drying at a temperature of 60°C and a drying time of 300 minutes.

[0197] The long tube was placed in boiling water. Under the impact of boiling water, the time for the long tube to be significantly deformed was recorded. The average value of the five groups of samples was 13 minutes.

[0198] The two sides of the long tube were clamped, and then slowly stretched at a rate of 20 mm / min until the long tube broke. The maximum tensile force was recorded, and the average value of the five groups of samples was 87 N.

[0199] 2. For molded materials:

[0200] S21. Raw material preparation:

[0201] The cellulose powder is one or a combination of two or more of straw powder, paper mulberry powder, bamboo powder and coconut shell powder in any proportion;

[0202] The cellulose powder includes a first cellulose powder with a particle size greater than 150 meshes, a second cellulose powder with a particle size not greater than 150 meshes and greater than 100 meshes, and a third cellulose powder with a particle size not greater than 100 meshes and greater than 60 meshes, wherein the first cellulose powder accounts for 30-35wt% and the second cellulose powder accounts for 30-35wt%, and the rest is the third cellulose powder;

[0203] The cellulose powder is prepared as follows: drying the raw material in a vacuum oven at 90-110° C. for 60-110 min;

[0204] Then, the dried sample is crushed by a high-speed crusher, and then sieved by a vibration screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder;

[0205] The cellulose fiber is one of cotton fiber, paper mulberry fiber, bamboo fiber, and hemp fiber, or a combination of two or more in any proportion, and the fiber length is 2 to 20 mm and the diameter is 20 to 1000 μm;

[0206] The cellulose particles are bamboo particles, wood particles or a mixture of the two in any proportion, and are crushed by a universal crusher or a wood crusher to a particle size of 5 to 30 mm and dried at 65 to 75°C.

[0207] The cellulose dissolving solution is prepared as follows:

[0208] Then, the pulp is placed in a specific solvent system, wherein the mass of the pulp input accounts for 5 to 10 wt% of the total mass of the specific solvent;

[0209] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6-8wt%, and the mass fraction of urea is 6-8wt%. The solvent system is precooled to -12°C to -7°C, the pulp is added in batches, and then stirred for 45-60 minutes to obtain a cellulose solution;

[0210] The pulp is cotton pulp or wood pulp.

[0211] The cellulose nanocrystals are obtained in the following manner:

[0212] The pulp is placed in a sulfuric acid solution with a mass fraction of 40-70wt%, the mass of the pulp is 5-10% of the mass of the sulfuric acid solution, the reaction temperature is 50-105°C, the reaction is stirred for 2-3 hours, then neutralized and washed, homogenized at 500-900bar for 1-3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15-25%.

[0213] The cellulose fiber is a mixture of one or more of cotton fiber, paper mulberry fiber, bamboo fiber, and hemp fiber in any proportion, the cellulose fiber has a length of 2 to 20 mm, a diameter of 20 to 1000 μm, and is dried at 45 to 55° C.

[0214] The fiber length of the cellulose nanofibers is 100 to 500 μm, and the diameter is 10 to 50 nm;

[0215] The cross-linking agent is a mixture of one or more of bentonite, polyvinyl alcohol, borax, starch, polyacrylamide, and waterborne polyurethane in any proportion;

[0216] The inorganic mineral powder is a mixture of one or more of quartz sand, talc, montmorillonite, wollastonite, kaolin, magnesium hydroxide and mica in any proportion, and the mesh number is 800-1500 meshes.

[0217] S22. Raw material mixing

[0218] 10 to 60 parts of cellulose solution, 10 to 20 parts of cellulose nanocrystals (i.e., cellulose nanocrystal slurry), 10 to 30 parts of cellulose powder, 1 to 5 parts of inorganic mineral powder, 5 to 15 parts of cellulose fibers, 10 to 50 parts of cellulose particles, and 10 to 20 parts of cellulose nanofibers are mixed evenly;

[0219] Then add 0.5 to 5 parts of a cross-linking agent and mix evenly to obtain an original slurry;

[0220] S23. Compression molding

[0221] The original slurry is placed in a mold for compression molding to obtain a sample, the molding pressure is 15-30 MPa, and the molding time is 30-100 s; the compression molding obtains a block with a thickness of 10 mm and a size of 100 mm*100 mm;

[0222] S24 post-molding treatment

[0223] The molded sample is immersed in a coagulation bath, and after the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, and the drying temperature is 50-90° C. The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12-15wt%, and the mass fraction of sodium sulfate is 18-25wt%;

[0224] The shaped block is placed in a vacuum oven for drying at a temperature of 60 to 90° C. for a drying time of 120 to 300 minutes.

[0225] Specifically do the following embodiments:

[0226] Embodiment 1:

[0227] S2101. Raw material preparation:

[0228] The cellulose powder is coconut shell powder;

[0229] The cellulose powder includes a first cellulose powder with a particle size greater than 150 meshes, a second cellulose powder with a particle size not greater than 150 meshes and greater than 100 meshes, and a third cellulose powder with a particle size not greater than 100 meshes and greater than 60 meshes, wherein the first cellulose powder accounts for 30wt%, the second cellulose powder accounts for 30wt%, and the rest is the third cellulose powder;

[0230] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 90° C. for 110 min;

[0231] Then, the dried sample is crushed by a high-speed crusher, and then sieved by a vibration screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder;

[0232] The cellulose fibers are cotton fibers with a fiber length of 2 to 20 mm and a diameter of 20 to 1000 μm;

[0233] The cellulose particles are bamboo particles, which are crushed by a universal crusher to a particle size of 5 to 30 mm and dried at 65° C. for 1 hour.

[0234] The cellulose dissolving solution is prepared as follows:

[0235] Then, the pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass of the specific solvent;

[0236] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0237] The pulp is cotton pulp.

[0238] The cellulose nanocrystals are obtained in the following manner:

[0239] The pulp was placed in a 40wt% sulfuric acid solution, the mass of the pulp was 5% of the mass of the sulfuric acid solution, the reaction temperature was 105°C, the reaction was stirred for 2 hours, then neutralized and washed, homogenized once at 500bar, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15%.

[0240] The cellulose fibers are cotton fibers, the length of the cellulose fibers is 2 to 20 mm, the diameter is 20 to 1000 μm, and they are dried at 45° C. for 1 hour;

[0241] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0242] The cross-linking agent is polyacrylamide;

[0243] The inorganic mineral powder is talc, and the mesh number is 800-1500 meshes.

[0244] S2102. Raw material mixing

[0245] Mix 10 parts of cellulose solution, 10 parts of cellulose nanocrystals (i.e., cellulose nanocrystal slurry), 10 parts of cellulose powder, 1 part of inorganic mineral powder, 5 parts of cellulose fibers, 10 parts of cellulose particles, and 10 parts of cellulose nanofibers evenly;

[0246] Then, 0.5 parts of a cross-linking agent was added and mixed evenly to obtain an original slurry;

[0247] S2103. Compression molding

[0248] The original slurry was placed in a mold for compression molding to obtain a sample, with a molding pressure of 15 MPa and a molding time of 100 s; a block with a thickness of 10 mm and a size of 100 mm*100 mm was obtained by compression molding;

[0249] S2104 post-molding treatment

[0250] The molded sample is immersed in a coagulation bath, and after the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, and the drying temperature is 50°C for 1h; the coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12wt% and the mass fraction of sodium sulfate is 18wt%;

[0251] The shaped block was placed in a vacuum oven for drying at a temperature of 60°C for 300 min.

[0252] The samples were cut into strips of 10 mm*100 mm, and then tested using a three-point bending apparatus until the material broke. The maximum bending force was recorded, and the average value of the five groups of samples was 650 N.

[0253] Embodiment 2:

[0254] S2201. Raw material preparation:

[0255] The cellulose powder is bamboo powder;

[0256] The cellulose powder includes a first cellulose powder with a particle size greater than 150 meshes, a second cellulose powder with a particle size not greater than 150 meshes and greater than 100 meshes, and a third cellulose powder with a particle size not greater than 100 meshes and greater than 60 meshes, wherein the first cellulose powder accounts for 35wt%, the second cellulose powder accounts for 35wt%, and the rest is the third cellulose powder;

[0257] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 110° C. for 60 minutes;

[0258] Then, the dried sample is crushed by a high-speed crusher, and then sieved by a vibration screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder;

[0259] The cellulose fibers are hemp fibers with a fiber length of 2 to 20 mm and a diameter of 20 to 1000 μm;

[0260] The cellulose particles are wood particles, which are crushed by a wood crusher to a particle size of 5 to 30 mm and dried at 75° C. for 1 hour.

[0261] The cellulose dissolving solution is prepared as follows:

[0262] Then, the pulp is placed in a specific solvent system, wherein the mass of the pulp input accounts for 5 to 10 wt% of the total mass of the specific solvent;

[0263] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 8wt%, and the mass fraction of urea is 8wt%. The solvent system is precooled to -7°C, the pulp is added in batches, and then stirred for 60 minutes to obtain a cellulose solution;

[0264] The pulp is wood pulp.

[0265] The cellulose nanocrystals are obtained in the following manner:

[0266] The pulp was placed in a 70wt% sulfuric acid solution, the mass of the pulp was 10% of the mass of the sulfuric acid solution, the reaction temperature was 50°C, the reaction was stirred for 3 hours, then neutralized and washed, homogenized at 900bar for 3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 25%.

[0267] The cellulose fiber is a mixture of one or more of cotton fiber, paper mulberry fiber, bamboo fiber, and hemp fiber in any proportion, the cellulose fiber has a length of 2 to 20 mm, a diameter of 20 to 1000 μm, and is dried at 55° C. for 1 hour;

[0268] The fiber length of the cellulose nanofibers is 100 to 500 μm, and the diameter is 10 to 50 nm;

[0269] The cross-linking agent is starch;

[0270] The inorganic mineral powder is talc, and the mesh number is 800-1500 meshes.

[0271] S2202. Raw material mixing

[0272] 60 parts of cellulose solution, 20 parts of cellulose nanocrystals (i.e., cellulose nanocrystal slurry), 30 parts of cellulose powder, 5 parts of inorganic mineral powder, 15 parts of cellulose fibers, 50 parts of cellulose particles, and 20 parts of cellulose nanofibers are mixed evenly;

[0273] Then add 5 parts of cross-linking agent and mix well to obtain the original slurry;

[0274] S2203. Compression molding

[0275] The original slurry was placed in a mold for compression molding to obtain a sample, with a molding pressure of 30 MPa and a molding time of 30 s; a block with a thickness of 10 mm and a size of 100 mm*100 mm was obtained by compression molding;

[0276] S2204 post-molding treatment

[0277] The molded sample is immersed in a coagulation bath, and after the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, and the drying temperature is 90°C for 1h; the coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 15wt% and the mass fraction of sodium sulfate is 25wt%;

[0278] The shaped blocks were placed in a vacuum oven for drying at 90°C for 120 min.

[0279] The samples were cut into strips of 10 mm*100 mm, and then tested using a three-point bending apparatus until the material broke. The maximum bending force was recorded, and the average value of the five groups of samples was 590 N.

[0280] Comparative Example 1:

[0281] S2301. Raw material preparation:

[0282] The cellulose powder is coconut shell powder;

[0283] The cellulose powder includes a first cellulose powder with a particle size greater than 150 meshes, a second cellulose powder with a particle size not greater than 150 meshes and greater than 100 meshes, and a third cellulose powder with a particle size not greater than 100 meshes and greater than 60 meshes, wherein the first cellulose powder accounts for 30wt%, the second cellulose powder accounts for 30wt%, and the rest is the third cellulose powder;

[0284] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 90° C. for 110 min;

[0285] Then, the dried sample is crushed by a high-speed crusher, and then sieved by a vibration screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder;

[0286] The cellulose fibers are cotton fibers with a fiber length of 2 to 20 mm and a diameter of 20 to 1000 μm;

[0287] The cellulose particles are bamboo particles, which are crushed by a universal crusher to a particle size of 5 to 30 mm and dried at 65° C. for 1 hour.

[0288] The cellulose dissolving solution is prepared as follows:

[0289] Then, the pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass of the specific solvent;

[0290] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0291] The pulp is cotton pulp.

[0292] The cellulose fibers are cotton fibers, the length of the cellulose fibers is 2 to 20 mm, the diameter is 20 to 1000 μm, and they are dried at 45° C. for 1 hour;

[0293] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0294] The cross-linking agent is polyacrylamide;

[0295] The inorganic mineral powder is talc, and the mesh number is 800-1500 meshes.

[0296] S2302. Raw material mixing

[0297] 10 parts of cellulose solution, 10 parts of cellulose nanocrystals (commercially available, 15 wt% concentration), 10 parts of cellulose powder, 1 part of inorganic mineral powder, 5 parts of cellulose fibers, 10 parts of cellulose particles, and 10 parts of cellulose nanofibers were mixed evenly;

[0298] Then, 0.5 parts of a cross-linking agent was added and mixed evenly to obtain an original slurry;

[0299] S2303. Compression molding

[0300] The original slurry was placed in a mold for compression molding to obtain a sample, with a molding pressure of 15 MPa and a molding time of 100 s; a block with a thickness of 10 mm and a size of 100 mm*100 mm was obtained by compression molding;

[0301] S2304 post-molding treatment

[0302] The molded sample is immersed in a coagulation bath, and after the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, and the drying temperature is 50°C for 1h; the coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12wt% and the mass fraction of sodium sulfate is 18wt%;

[0303] The shaped block was placed in a vacuum oven for drying at a temperature of 60°C for 300 min.

[0304] The samples were cut into strips of 10 mm*100 mm, and then tested using a three-point bending apparatus until the material broke. The maximum bending force was recorded, and the average value of the five groups of samples was found to be 450 N.

[0305] Comparative Example 2:

[0306] S2401. Raw material preparation:

[0307] The cellulose powder is coconut shell powder;

[0308] The particle size of the cellulose powder is greater than 150 mesh;

[0309] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 90° C. for 110 min;

[0310] Then, the dried sample is crushed by a high-speed crusher, and then sieved by a vibrating screen to obtain cellulose powder;

[0311] The cellulose fibers are cotton fibers with a fiber length of 2 to 20 mm and a diameter of 20 to 1000 μm;

[0312] The cellulose particles are bamboo particles, which are crushed by a universal crusher to a particle size of 5 to 30 mm and dried at 65° C. for 1 hour.

[0313] The cellulose dissolving solution is prepared as follows:

[0314] Then, the pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass of the specific solvent;

[0315] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0316] The pulp is cotton pulp.

[0317] The cellulose nanocrystals are obtained in the following manner:

[0318] The pulp was placed in a 40wt% sulfuric acid solution, the mass of the pulp was 5% of the mass of the sulfuric acid solution, the reaction temperature was 105°C, the reaction was stirred for 2 hours, then neutralized and washed, homogenized once at 500bar, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15%.

[0319] The cellulose fibers are cotton fibers, the length of the cellulose fibers is 2 to 20 mm, the diameter is 20 to 1000 μm, and they are dried at 45° C. for 1 hour;

[0320] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0321] The cross-linking agent is polyacrylamide;

[0322] The inorganic mineral powder is talc, and the mesh number is 800-1500 meshes.

[0323] S2402. Raw material mixing

[0324] Mix 10 parts of cellulose solution, 10 parts of cellulose nanocrystals (i.e., cellulose nanocrystal slurry), 10 parts of cellulose powder, 1 part of inorganic mineral powder, 5 parts of cellulose fibers, 10 parts of cellulose particles, and 10 parts of cellulose nanofibers evenly;

[0325] Then, 0.5 parts of a cross-linking agent was added and mixed evenly to obtain an original slurry;

[0326] S2403. Compression molding

[0327] The original slurry was placed in a mold for compression molding to obtain a sample, with a molding pressure of 15 MPa and a molding time of 100 s; a block with a thickness of 10 mm and a size of 100 mm*100 mm was obtained by compression molding;

[0328] S2404 post-molding treatment

[0329] The molded sample is immersed in a coagulation bath, and after the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, and the drying temperature is 50°C for 1h; the coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12wt% and the mass fraction of sodium sulfate is 18wt%;

[0330] The shaped block was placed in a vacuum oven for drying at a temperature of 60°C for 300 min.

[0331] The samples were cut into strips of 10 mm*100 mm, and then tested using a three-point bending apparatus until the material broke. The maximum bending force was recorded, and the average value of the five groups of samples was 530 N.

[0332] Comparative Example 3:

[0333] S2501. Raw material preparation:

[0334] The cellulose powder is coconut shell powder;

[0335] The cellulose powder includes a first cellulose powder with a particle size greater than 150 meshes, a second cellulose powder with a particle size not greater than 150 meshes and greater than 100 meshes, and a third cellulose powder with a particle size not greater than 100 meshes and greater than 60 meshes, wherein the first cellulose powder accounts for 30wt%, the second cellulose powder accounts for 30wt%, and the rest is the third cellulose powder;

[0336] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 90° C. for 110 min;

[0337] Then, the dried sample is crushed by a high-speed crusher, and then sieved by a vibration screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder;

[0338] The cellulose fibers are cotton fibers with a fiber length of 2 to 20 mm and a diameter of 20 to 1000 μm;

[0339] The cellulose particles are bamboo particles, which are crushed by a universal crusher to a particle size of 5 to 30 mm and dried at 65° C. for 1 hour.

[0340] The cellulose dissolving solution is prepared as follows:

[0341] Then, the pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass of the specific solvent;

[0342] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0343] The pulp is cotton pulp.

[0344] The cellulose nanocrystals are obtained in the following manner:

[0345] The pulp was placed in a 40wt% sulfuric acid solution, the mass of the pulp was 5% of the mass of the sulfuric acid solution, the reaction temperature was 105°C, the reaction was stirred for 2 hours, then neutralized and washed, homogenized once at 500bar, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15%.

[0346] The cellulose fibers are cotton fibers, the length of the cellulose fibers is 2 to 20 mm, the diameter is 20 to 1000 μm, and they are dried at 45° C. for 1 hour;

[0347] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0348] The cross-linking agent is polyacrylamide;

[0349] The inorganic mineral powder is talc, and the mesh number is 800-1500 meshes.

[0350] S2502. Raw material mixing

[0351] Mix 10 parts of cellulose solution, 10 parts of cellulose nanocrystals (i.e., cellulose nanocrystal slurry), 10 parts of cellulose powder, 1 part of inorganic mineral powder, 5 parts of cellulose fibers, 10 parts of cellulose particles, and 10 parts of cellulose nanofibers evenly;

[0352] Then, 0.5 parts of a cross-linking agent was added and mixed evenly to obtain an original slurry;

[0353] S2503. Compression molding

[0354] The original slurry was placed in a mold for compression molding to obtain a sample, with a molding pressure of 15 MPa and a molding time of 100 s; a block with a thickness of 10 mm and a size of 100 mm*100 mm was obtained by compression molding;

[0355] S2504 post-molding treatment

[0356] The block was placed in a vacuum oven for drying at a temperature of 60°C for 300 min.

[0357] The samples were cut into strips of 10 mm*100 mm, and then tested using a three-point bending apparatus until the material broke. The maximum bending force was recorded, and the average value of the five groups of samples was found to be 120 N.

[0358] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included within the scope of the claims of the present application.

Claims

1. A cellulose plastic material, characterized in that: Including the following raw materials by mass: Cellulose powder: 10-50 parts; Inorganic mineral powder: 1-5 parts; Cellulose nanofibers: 10-50 parts; Cellulose nanocrystals: 10-50 parts; Cellulose dissolving solution: 10-60 parts; Cross-linking agent: 0.5 to 5 parts.

2. A cellulose plastic material according to claim 1, characterized in that: The mesh number of the cellulose powder particle size is greater than 150 meshes.

3. A cellulose plastic material according to claim 2, characterized in that: The cellulose powder is one or a combination of bleached wood pulp powder and cotton pulp powder; The cellulose powder is prepared as follows: drying the raw material in a vacuum oven at 90-110° C. for 60-110 min; The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain cellulose powder with a particle size greater than 150 meshes.

4. A cellulose plastic material according to claim 1, characterized in that: The cellulose dissolving solution is prepared as follows: Then, the pulp is placed in a specific solvent system, wherein the mass of the pulp input accounts for 5 to 10 wt% of the total mass of the specific solvent; The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6-8wt%, and the mass fraction of urea is 6-8wt%; the solvent system is precooled to -12°C to -7°C, the pulp is added in batches, and then stirred for 45-60 minutes to obtain a cellulose solution; The pulp is cotton pulp or wood pulp; The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

5. A cellulose plastic material according to claim 4, characterized in that: The cellulose nanocrystals are obtained in the following manner: The pulp is placed in a sulfuric acid solution with a mass fraction of 40-70wt%, the mass of the pulp is 5-10% of the mass of the sulfuric acid solution, the reaction temperature is 50-105°C, the reaction is stirred for 2-3 hours, then neutralized and washed, homogenized at 500-900bar for 1-3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15-25%.

6. The cellulose plastic material according to claim 1, characterized in that: It also includes the following raw materials in parts by weight: Cellulose fiber: 5-15 parts; Cellulose particles: 10-50 parts; The cellulose powder: 10 to 30 parts; The cellulose nanofibers: 10 to 20 parts; The cellulose nanocrystals: 10 to 20 parts.

7. A cellulose plastic material according to claim 6, characterized in that: The cellulose fiber is a mixture of one or more of cotton fiber, paper mulberry fiber, bamboo fiber, and hemp fiber in any proportion, the cellulose fiber has a length of 2 to 20 mm, a diameter of 20 to 1000 μm, and is dried at 45 to 55° C. The cellulose powder includes a first cellulose powder with a particle size greater than 150 meshes, a second cellulose powder with a particle size not greater than 150 meshes and greater than 100 meshes, and a third cellulose powder with a particle size not greater than 100 meshes and greater than 60 meshes, wherein the first cellulose powder accounts for 30-35wt% and the second cellulose powder accounts for 30-35wt%, and the rest is the third cellulose powder; The cellulose powder is one or a combination of two or more of straw powder, paper mulberry powder, bamboo powder and coconut shell powder in any proportion; The cellulose powder is prepared as follows: drying the raw material in a vacuum oven at 90-110° C. for 60-110 min; Then, the dried sample is crushed by a high-speed crusher, and then sieved by a vibration screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder; The cellulose fiber is one of cotton fiber, paper mulberry fiber, bamboo fiber, and hemp fiber, or a combination of two or more in any proportion, and the fiber length is 2 to 20 mm and the diameter is 20 to 1000 μm; The cellulose particles are bamboo particles, wood particles or a mixture of the two in any proportion, and are crushed by a universal crusher or a wood crusher to a particle size of 5 to 30 mm and dried at 65 to 75°C.

8. The cellulose plastic material according to claim 1, characterized in that: The cross-linking agent is a mixture of one or more of bentonite, polyvinyl alcohol, borax, starch, polyacrylamide, and waterborne polyurethane in any proportion; The inorganic mineral powder is a mixture of one or more of quartz sand, talc, montmorillonite, wollastonite, kaolin, magnesium hydroxide and mica in any proportion, and the mesh number is 800-1500 meshes.

9. A method for using the cellulose plastic material according to claim 5, characterized in that: The steps include: The cellulose solution, cellulose powder, inorganic mineral powder, cellulose nanofibers and cellulose nanocrystals are mixed and stirred evenly; Then, a cross-linking agent is added and mixed evenly to obtain an original slurry; After degassing the original slurry, load it into the barrel of the 3D printer and print it according to the set program; the diameter of the extrusion nozzle used for printing is 0.5mm, the extrusion pressure is 0.2MPa, and the extrusion nozzle moving speed is 50mm / s; The printed sample is placed in a coagulation bath, and after the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, and the drying temperature is 50-90° C. The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12-15wt%, and the mass fraction of sodium sulfate is 18-25wt%; Soaking and washing away the residual sulfuric acid and salt in water can obtain the finalized 3D printing material; The shaped 3D printing material is placed in a cross-linking solution, wherein the cross-linking solution is K + , Ca 2+ , Fe 3+ 、Zn 2+ , Cu 2+ 、Al 3+ A mixed solution of one or more soluble salts in the mixture is prepared with a concentration of 0.5 to 2 mol / L; the cross-linking temperature is 25 to 35°C for 8 to 12 hours, and then the mixture is washed and dried in a vacuum oven at a temperature of 60 to 90°C for 120 to 300 minutes.

10. A method for using the cellulose plastic material according to claim 8, characterized in that: The steps include: The cellulose solution, cellulose powder, inorganic mineral powder, cellulose nanofibers, cellulose nanocrystals, cellulose fibers and cellulose particles are mixed and stirred evenly; Then, a cross-linking agent is added and mixed evenly to obtain an original slurry; The original slurry is placed in a mold for compression molding to obtain a sample, the molding pressure is 15-30 MPa, and the molding time is 30-100 s; The molded sample is immersed in a coagulation bath, and after the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, and the drying temperature is 50-90° C. The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12-15wt%, and the mass fraction of sodium sulfate is 18-25wt%; The shaped drying composite material is placed in a vacuum oven for drying at a temperature of 60 to 90° C. for a drying time of 120 to 300 minutes.